DETERMINAN MINAT BELI PADA E-COMMERCE SHOPEE DALAM PERSPEKTIF PERILAKU KONSUMEN ISLAM - Rindy Okky Eka Putri; Mohammad Dliyaul Muflihin; Ade Irma Suryani Lating; Maziyah Mazza Basya (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This research was conducted to find out how affiliate marketing and online promotions influence the purchasing interest of Shopee e-commerce users from the perspective of Islamic consumer behavior. With primary data obtained through questionnaires and the number of samples used was 100 respondents using purposive sampling techniques. In processing and analyzing the data, SPSS version 27 software was used through multiple linear regression analysis tests. The test results are that affiliate marketing and online promotions partially or simultaneously have a positive and significant influence on consumer buying interest of Shopee e-commerce users. However, in Islamic consumer behavior, the level of purchasing interest must still be adjusted to Islamic values and principles of Islamic consumption. These include making purchases of halal and good products, when making purchases, Islamic consumers are not easily influenced by promotions, buy products that suit their needs, and avoid unplanned purchases. This is the difference between Islamic consumption behavior and conventional consumption behavior.